Microfinance Investors Adjust Strategy in Tougher Market Conditions - Glisovic, Jasmina; Reille, Xavier (Washington, DC: World Bank, 2012)
Microfinance Investment Vehicles (MIVs) in 2010 are confronting the most challenging investment environment since the 1990s. Over the past two years, microfinance investors witnessed a handful of debt defaults and a major slowdown in demand for capital from microfinance institutions (MFIs) a sharp contrast after the heady market growth experienced in previous years. However, MIVs continue to grow and earn positive returns. This brief presents the major trends within the MIV sector to emerge from this year's Consultative Group to Assist The Poorest (CGAP) MIV survey, powered by Symbiotic. It also highlights the growing commitment among MIVs to sound environment, social, and governance (ESG) practices. The last section discusses MIV challenges and prospects.